Archaea in Organic-Lean and Organic-Rich Marine Subsurface Sediments: An Environmental Gradient Reflected in Distinct Phylogenetic Lineages - Durbin, Alan M.; Teske, Andreas (Frontiers in Microbiology, 2012)
Examining the patterns of archaeal diversity in little-explored organic-lean marine subsurface sediments presents an opportunity to study the association of phylogenetic affiliation and habitat preference in uncultured marine Archaea. Here we have compiled and re-analyzed published archaeal 16S rRNA clone library datasets across a spectrum of sediment trophic states characterized by a wide range of terminal electron-accepting processes. Our results show that organic-lean marine sediments in deep marine basins and oligotrophic open ocean locations are inhabited by distinct lineages of archaea that are not found in the more frequently studied, organic-rich continental margin sediments. We hypothesize that different combinations of electron donor and acceptor concentrations along the organic-rich/organic-lean spectrum result in distinct archaeal communities, and propose an integrated classification of habitat characteristics and archaeal community structure.